Pokémon GO: snake oil or miracle cure for physical inactivity? - Chaput, Jean-Philippe; LeBlanc, Allana G. (Annals of Translational Medicine, 2017)
The term “snake oil” was popularized in the early 1900s as a miracle cure-all, and later, after uncovering that it was made up of no more than mineral water and turpentine, it was coined as a term for someone selling products with fraudulent, questionable, or unverifiable benefits (1). Pokémon GO, released in July 2016, quickly became the world’s most downloaded smartphone application, surpassing Twitter and Candy Crush within the first two weeks of its release (2). Initial reports and anecdotal evidence suggested that Pokémon GO might be the panacea researchers have been searching for to solve the global physical inactivity crisis. However, less than a year later, we understand that after the initial excitement subsided, Pikachu was not able maintain an increase in habitual physical activity. Pokémon GO may be just snake oil.